Dr. Antonio Bascones Martínez a paragon of latin american and spanish stomatology - Ramos Perfecto, Donald (2019)
The renowned Dr. Antonio Bascones Martínez, represents an exponent of contemporary dentistry, his knowledge and experience offered in his classes; make him the epitome of this profession. At 74 years old, he reminds us of the ever-changing evolution of dentistry. In this interview we want to recollect his story, inspiration, highlight his abundant knowledge and regard him as the teacher he is.